On Innovation, creativity, and international trade: Theoretical linkages, empirical evidence, and the database on IPRs in trade agreements - Puutio, Teemu Alexander (fi=Turun yliopisto|en=University of Turku|, 2022)
This study was motivated by a simple question: do international intellectual property norms affect the development trajectories of developing nations and if so, in what ways? While hunting an answer to this query, a multitude of interconnected questions were unearthed: some were answered, while others were left for future researchers to explore. All told, ten independent articles were published, of which six have been selected for inclusion in the work at hand. Together, these articles explore the theoretical linkages between creativity, innovation, intellectual property rights (IPRs) and trade, assess the role of trade agreements in creating and transplanting international IPRs norms, map out the topography of IPRs norms in modern trade agreements, and chart a path towards policies with which developing countries can ensure that the IPRs norms that they choose to adopt are for their own benefit. The study focuses on the countries of the Asia-Pacific and it explores how creative economies can be established, fostered, and sustained in the presence of IPRs norms and institutions. The study’s main focus of analysis became trade agreements in all of their forms, through which the majority of recent international IPRs norms have been established, transplanted, and spread across the Asia-Pacific region. In terms of results, the study shows that IPRs norms have clear theoretical pathways through which they impact economic, social, creative, and environmental development trajectories. The database complied by the author, “IPRs in Trade Agreements: An assessment of strength and complexity,” best demonstrates how these pathways are utilized in action and encompasses all publicly available trade agreements, including IPRs provisions. Each agreement was carefully assessed against an objective framework of analysis, according to which the relative strength of each provision was established. The work to further develop and utilize the database continues with the assistance of collaborative partners such as the United Nations and WTO. The study concludes with a handbook on negotiating development-oriented IPRs-inclusive trade agreements, issued for the benefit of policymakers, legal researchers, and trade negotiators from developing countries in the Asia-Pacific.

--- Tämä teos pyrkii vastaamaan yksinkertaiselta kuulostavaan kysymykseen: vaikuttavatko kansainväliset immateriaalioikeudelliset säännökset kehittyvien maiden kehitysmahdollisuuksiin, ja jos, niin millä tavoin? Vastauksen etsimisen lomassa heräsi useita uusia toinen toistaan mielenkiintoisempia kysymyksiä, joista osaan tämä teos tarjoaa vastauksen ja osa on jätetty tulevia tutkimuksia varten. Kaiken kaikkeaan tämä teos koostuu kuudesta erikseen julkaistusta artikkelista, jotka on valittu tätä teosta varten kymmenen tutkimuksen aikana julkaistun artikkelin joukosta. Yhdessä nämä artikkelit selvittävät luovuuden, innovaation sekä immateriaalioikeuksien yhteyksiä, kartoittavat kansainvälisten kauppasopimusten immateriaalioikeussisältöjä sekä etsivät polkuja joita pitkin kehittyvät maat voivat kulkea kohti tulevaisuutta missä immateriaalioikeudet tukevat kansallista kestävää kehitystä. Tutkimuksen kohteeksi valikoitui Aasian ja Tyynenmeren valtiot, ja mukaan otetut teokset käsittelevät erityisesti kysymystä siitä, miten näiden maiden ‘luovia talouksia’ on mahdollista tukea kansainvälisten immateriaaliokeusnormiston kautta. Multilateraalisten immateriaalioikeus foorumien viimeaikaisen heikon toimintakyvyn johdosta tämä tutkimus keskittyi kansainvälisiin kauppasopimuksiin joiden kautta suurin osa kansainvälisistä immateriaalioikeusnormeista on löytänyt tiensä Aasian ja Tyynenmeren kehittyviin maihin. Tämän teoksen tärkein lopputulos on “IPRs in Trade Agreements: An assessment of strength and complexity” niminen tietokanta, mihin on kodifioitu jokaisen saatavilla olevan kansainvälinen kauppasopimuksen immateriaalioikeussisältö. Tietokanta perustuu objektiiviseen arviointiviitekehykseen, ja työ sekä tämän viitekehyksen että tietokannan kehittämiseksi jatkuu mm. YK:n sekä Maailman Kauppajärjestön kanssa. Tämä teos päättyy Aasian ja Tyynenmeren kehittyvien maiden immateriaalioikeussääntelyn tueksi kehitettyyn käsikirjaan, jonka tarkoituksena on auttaa päättäjiä, tutkijoita sekä kauppaneuvottelijoita löytämään teitä entistä kestävimpien immateriaalioikeusnormien luokse kansainvälisten kauppasopimusten kautta.